Exemplarity in the Public Realm. Issue 3 (2nd September 2018) - Ferrara, Alessandro
Abstract: The role of exemplarity in the public realm is explored from a threefold angle. After introducing briefly the notion of exemplarity as distinct from "being an example of, " as possessed of a normative force resting on its potential for disclosure, and as connected with a sense of the human flourishing, two junctures are singled out at which exemplarity plays a significant role in contemporary political theory. First, John Rawls's notion of the reasonable, understood as a quality of the political actor and as a standard for public reason, and especially as it occurs in the phrase "most reasonable for us, " predicated of justice as fairness as a political conception of justice, is shown to presuppose the normativity of exemplarity if "public reason" is to remain distinct from "practical reason." Second, in his recently published The Civil Rights Revolution (2014 – the third volume of We the People ), Bruce Ackerman shows that 20th-century "constitutional moments, " starting from the New Deal, no longer follow the scripted Article Five-based path of constitutional amendment. They are ignited and unfold on the basis of "landmark statutes" (such as the New Deal legislation, the Civil Rights Act, the Fair Housing Act) and judicial "exemplary superprecedents" (such as Brown or Loving ). This reconstruction of the new dynamics of constitutional change in US recent history prompts the question about the nature of "landmarkness" of both congressional statutes and Supreme Court pronouncements. The paper highlights the relation of landmarkness to exemplarity. Third, exemplarity in the public realm is then contrasted with other forms of exemplarity. Its specific nature is highlighted and four versions of public exemplarity are distinguished: exemplarity of the deed; of the personality; of a legal notion; of a constitutional order.